Constitutional law of India - Mahajan, V.D. (Lucknow, 1984)
This book is primarily meant for LL.B. and LL.M. students of the Indian Universities but it will also be found useful by students of political science and also those preparing for various competitive examinations in the country.
Keywords: Constitutional law-India